THE INFLUENCE OF BUDGET, SPI, AND COMPETENCE OF VILLAGE APPARATUSES ON THE ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT AND THEIR IMPACT ON WELFARE - Muhammad Saifrizal; Koko Bustami (Jurnal Ekonomi, 2022)
The Village Fund is a mandate from the law as stipulated in Article 72 Paragraph 2 of Law Number 6 of 2014. the central government is obliged to allocate Village Funds in the State Budget (APBN). Policies for allocating and distributing Village Funds by taking into account village characteristics and village performance in managing Village Funds. The purpose of this research is to look at the determination of the clarity of budget targets, the internal control system and the competency of the village apparatus in terms of accountability in managing village funds and their impact on village welfare.This research model usesPath Analysisfor testing a direct and indirect effect. The results of this study prove that budget targets, internal control systems and competence of village apparatus have a direct influence on accountability. Likewise with the results of indirect influence, only the internal control system which does not have an indirect effect on village welfare. For the functioning of these variables, accountability for village fund management has a direct effect on village welfare